PERBANDINGAN PENGENDALIAN KUALITAS PRODUK WALL DISPLAY DENGAN DIAGRAM KENDALI D^2 DAN T^2 HOTELLING - Harahap, Sherly Vitara; br Tarigan, Ernita Dewi; Sembiring, Pasukat; Pane, Rahmawati (MES: Journal of Mathematics Education and Science, 2024)
Quality control is the application of a statistical model of quality control to collect and analyze data to evaluate and monitor production results. Melia Frame Calligraphy is an agent and manufacturer of frames or frame bars and finished frameworks made from fiber and wood. The best-selling product is the wall display. Although wall displays are in high demand, they are also the most returned products due to defects since 2023. Based on observation data, it is calculated that the product defect data is quite high, with an average total of 34 defects per day. This study aims to detect the quality of wall display products with  (Mahalanobis Distance) and  Hotelling control charts at Melia Frame Calligraphy Trade Business. The results of this study found that the product experienced the most defects in October 2023 with a total defective product of 1009 units. By using the control diagram, 20 observations out of a total of 75 observations are outside the control limits, then by using the control diagram, 2 observations out of a total of 75 observations are outside the control limits. This shows that the wall display production process is not yet under control. These observations show that the  (Mahalanobis Distance) control chart has more sensitive control limits than the  Hotelling control chart control limits.